The case for protoconcepts: Why concepts, language, and protolanguage all need protoconcepts - Parthemore, Joel (Theoria et Historia Scientiarum, 2015)
Fodor is infamous for his radical conceptual nativism, McDowell likewise well-known for suggesting that concepts extend “all the way out” into the world and arguing against what he calls (per Sellars) The Myth of the Given: the idea that non-conceptual percepts justify conceptual frameworks. One need not go so far as either researcher, however, in allowing merit to their arguments. It seems we are predisposed, from the beginning of our lives, to look at the world in certain ways and not others. The world need not be “fully conceptual” to be never entirely free, for the conceptually minded agent, of conceptual taint. It seems structured remarkably like our concepts are structured because our concepts present it that way, and our concepts present it that way because of predispositions that are substantively innate. The Protoconcept Hypothesis holds that such protoconcepts are onto- and phylogenetically prior to concepts, themselves onto- and phylogenetically prior to (proto-)language. If that is right, then an account of language genesis and evolution requires a corresponding account for concepts and an explication of protolanguage assumes an explication of protoconcepts.